Analisis Motif Kain Tradisional Indonesia: Pemaknaan Visualisasi Abstrak hingga Naturalis - Ira Adriati Winarno (Universitas PGRI Adi Buana Surabaya, 2017)
Indonesia is a country with various cultures. One of cultural product that interesting to be analysis is textile.Indonesian traditional textiles are made by weaving and batik techniques. Traditional textiles have a deepphilosophical meaning related to the human existence in the universe. Traditional textiles have various motifs. It isinteresting to analyze the meaning of the motifs of Indonesian traditional textile. The approaches of this research aretraditional Indonesian aesthetics and cultural approach. Traditional textile motifs can be categorized into geometrics,figurative, and naturalist motifs. The motifs are influenced by textile making techniques. For instance, weavingtechnique has limitation in motif type. Weaving technique produces geometrics motif. The other technique is batik thathas freedom to produce various motifs for textile. The original Indonesian textile motifs generally are abstract motives.Figurative and naturalist motifs emerge after the entrance of other culture influence. Based on visualization analysis,abstract motif has deep meaning related to people life philosophy. Some of figurative motifs have philosophical meaning,but naturalist motifs generally do not have philosophical meaning in Indonesian people.